Health disparities in outcomes of pediatric systemic lupus erythematosus - Vara, Emily; Gilbert, Mileka; Ruth, Natasha M. (Frontiers in Pediatrics, 2022)
Healthcare disparities exist throughout the United States, and disparities in healthcare delivery are responsible for a substantial portion of preventable morbidity and mortality.1 SLE disproportionately affects racial and ethnic minoritized groups, including Blacks, Hispanics, and Asians/Pacific Islanders. Specifically, Black females have a three to four-fold increased risk of developing SLE than White females.2,3 Population studies funded through the Centers for Disease Control have examined variations in disease outcomes among the different populations around the United States. For example, studies have shown that lupus nephritis, anti-phospholipid syndrome, and thrombocytopenia are more likely to affect racial and ethnic minorities than Caucasians.3-5 In addition, the Center for Disease Control WONDER (Wide-ranging Online Data for Epidemiologic Research) database found SLE was the seventh leading cause of death for all women aged 15-25 years and the fifth leading cause of death for African American and Hispanic females. From these studies, we know SLE primarily affects racial and ethnic minorities, but we do not know why these groups are at increased risk of developing the disease or have worse outcomes. By examining the underlying mechanisms of health disparities within our patient populations and mitigation strategies, we will further understand and provide better treatment for our patients. This review will discuss current research related to health disparities and health outcomes in childhood-onset SLE (cSLE).